On-farm reproduction management in bovines paid big dividends - Kumar, Suresh; Pande, Megha; Chand, Naimi; Saha, S; Prasad, Naresh; Dubey, Shantanu Kumar (Indian Farming, 2022)
The experiences of the success cases revealed that the breeding disorders have reduced the productivity of cattle and thus the true potential of dairy has not been realised. Implementation of the interventions helped farmers increase productivity to a great extent. The timely interventions for heat detection and supporting services are essential. The interventions demonstrated successfully ought to be outscaled by the concerned line department.